Итоги охранных раскопок Западного некрополя Херсонеса Таврического в 1995 г. - Магда, А.В.; Дмитриев, В.А. (My University, 1997)
Magda A. V., Dmitriev V. A. Results of Security Excavation of West Necropolis in Chersonesus of Tauride in 1995